Tracking devices: On the reception of a novel security good. (February 2015) - Thumala, Angélica; Goold, Benjamin; Loader, Ian
In this article, we describe and make sense of the reception of a novel security good: namely, the personal GPS tracking device. There is nothing new about tracking. Electronic monitoring is an established technology with many taken-for-granted uses. Against this backdrop, we focus on a particular juncture in the 'social life' of tracking, the moment at which personal trackers were novel goods in the early stages of being brought to market and promoted as protective devices. Using data generated in a wider study of security consumption, our concern is to understand how this extension of tracking technology into everyday routines and social relations was received by its intended consumers and users. How do potential buyers or users respond to these novel protective devices? What is seductive or repulsive about keeping track of those towards whom one has a duty or relationship of care? How do new tracking technologies intersect with – challenge, reshape or get pushed back by – existing social practices and norms, most obviously around questions of risk, responsibility, trust, autonomy and privacy? This article sets out to answer these questions and to consider what the reception of this novel commodity can tell us about the meaning and future of security.